(untitled) (Journal of the College of Education for Women, 2018)
Coconut milk is considered as a natural drink that enhances the immunity and it is enriched by calcium, iron, magnesium and vitamin (C) and it is also safe drink for kids and bacterial anti-oxdant, and it may be used in the natural juices instead of the whole milk (cow milk) which is added to some juices. This study aimed to determine the nutritrnal value and the sensory evaluation properties of the natural orange juice enriched by canned coconut milk The result of the chemical analysis showed presence of statistically significant differences (p<0.05) between the treatments in protein and saccharides ratios ,and the (A4) treatment (30% of the cauued coconut milk addition) gave the highest protein ratio between the treatments and it reached 0.39% while in total saccharides ratio was at its highest ratio in (A) treatment (control treatment) among the treatment and it reached 7.68% .Mineral elements analysis results showed significant superiority of (A4) treatment in iron , magnesium and calcium contents in which they reached 2.01 , 32.54 and 24.06 mg per 100 gram respectively. The physical properties results showed a highest total soluble materials in (A) treatment (control treatment) and it reached 13.70, while pH values ranged between 3.8 to 6.0 in A and A1 treatments respectively. The sensory evaluation results referred to that (A) (control treatment) got the highest sensory evaluation marks followed by A1 (treatment) (10% coconut milk addition) and it was the more acceptance treatment for the kids also and adults.